Silent Hypertensive Crisis in an Adolescent: First Case Report of Pediatric Pheochromocytoma from Indonesia - Cahyani Gita Ambarsari; Eka Laksmi Hidayati; Bambang Tridjaja; Chaidir Arif Mochtar; Haryanti Fauzia Wulandari; Agnes Stephanie Harahap; Angela Grace (SAGE Publishing, 2021)
Secondary hypertension in children, to the rare extent, can be caused by endocrine factors such as pheochromocytoma, an adrenal tumor that secretes catecholamine. Only a few cases have been reported in the past 3 decades. To the best of our knowledge, this is the first case report of pediatric pheochromocytoma from Indonesia. We reviewed a case of a 16-year-old Indonesian boy with history of silent hypertensive crisis who was referred from a remote area in an island to the pediatric nephrology clinic at Cipto Mangunkusumo Hospital, Jakarta, Indonesia. Despite medications, his symptoms persisted for 14 months. At the pediatric nephrology clinic, pheochromocytoma was suspected due to symptoms of catecholamine secretion presented, which was palpitation, diaphoresis, and weight loss. However, as the urine catecholamine test was unavailable in Indonesia, the urine sample was sent to a laboratory outside the country. The elevated level of urine metanephrine, focal pathological uptake in the right adrenal mass seen on 131 I-MIBG, and histopathology examination confirmed the suspicion of pheochromocytoma. Following the tumor resection, he has been living with normal blood pressure without antihypertensive medications. This case highlights that pheochromocytoma should always be included in the differential diagnoses of any atypical presentation of hypertension. In limited resources setting, high clinical awareness of pheochromocytoma is required to facilitate prompt referral. Suspicion of pheochromocytoma should be followed by measurement of urine metanephrine levels. Early diagnosis of pheochromocytoma would fasten the optimal cure, alleviate the symptoms of catecholamine release, and reverse hypertension.